2019
DOI: 10.1177/0735633119884213
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Students’ Biology Learning by Using Augmented Reality as a Learning Supplement

Abstract: The purpose of this study was to investigate the effects of augmented reality (AR) technology on students’ learning outcomes (measured according to Bloom’s cognitive levels) and attitude toward biology. The print book was redesigned by integrating a form of AR into it. A quasi-experimental pretest and posttest designs were used to test the effectiveness of the developed book on learning outcomes and attitude toward biology. In addition, the students’ opinions about the AR technology and the redesigned book wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 36 publications
1
62
0
Order By: Relevance
“…Biology is defined as a set of knowledge about objects and natural phenomena obtained from the results of the thoughts and investigations of scientists conducted with experimental skills [14]. This definition implies that biology is a branch of knowledge that is built based on observations and classifications, usually arranged and verified, which involves the application of reasoning and data analysis to phenomena that occur in nature [14], [15].…”
Section: Biology Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Biology is defined as a set of knowledge about objects and natural phenomena obtained from the results of the thoughts and investigations of scientists conducted with experimental skills [14]. This definition implies that biology is a branch of knowledge that is built based on observations and classifications, usually arranged and verified, which involves the application of reasoning and data analysis to phenomena that occur in nature [14], [15].…”
Section: Biology Learningmentioning
confidence: 99%
“…The essence of biology is a science that uses nature with all its contents, including earth, plants, animals, and humans as its object of observations. Biology is a science that is obtained by using methods based on the representation of how to find out about nature so that biology is not only about mastering a set of knowledge in the form of facts, concepts, or principles, but also a process of discovery [14], [16].…”
Section: Biology Learningmentioning
confidence: 99%
“…One study compared the learning performance between students learning biology using an AR application and a 354 | P a g e www.ijacsa.thesai.org printed book [6]. Their study showed no difference in understanding and remembering factors between the students in both categories.…”
Section: Learning Tool For Microorganismsmentioning
confidence: 99%
“…According to some studies [6], [8], [9], a learning application should consider including multiple media to attract students' attention, such as video, audio, graphic, text and animation. The lengthy and dense text should be avoided as much as possible.…”
Section: Learning Tool For Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation